Heart Failure Status among Acute Ischemic Stroke Patients: A Hospital-Based Study - Fatemeh Ravandi; Arsh Haj Mohamad Ebrahim Ketabforoush; Fereshteh Azedi; Mohsen Hoshyarkhani; Farimah Fayyaz; Nahid Abbasi Khoshsirat (Neurology Research International)
Background. Since heart failure (HF) and ischemic stroke have common risk factors, their concurrent occurrence is likely. Strokes in HF patients could be life-threatening and lead to severe disabilities, longer hospitalization time, and mortality. The present study aims to investigate the prevalence of HF and its severity based on ejection fraction (EF) in patients with acute ischemic stroke. Methods. The present cross-sectional study included acute ischemic stroke patients admitted to Shahid Rajaei hospital in Karaj in 2020–2021. The diagnosis of HF was based on transthoracic echocardiography within 48 hours of symptom onset, and HF was classified into two groups: 41–49% as mildly reduced EF (HFmrEF) and ≤40% as reduced EF (HFrEF). Patients who did not complete cardiac studies were excluded. Results. 257 acute ischemic stroke patients (62.6% male) were included. Among stroke patients, the prevalence of HF, including HFrEF and HFmrEF, was 30.0% (95% CI: 21.4–38.6). HFmrEF and HFrEF was diagnosed in 32 (12.5%) and 45 (17.5%) patients, respectively. HF was significantly associated with older age, hypertension, past myocardial infarction (MI), and arrhythmia. A history of previous MI significantly increased the odds of heart failure (OR: 3.25, 95% CI: 1.82–5.81). Conclusion. There is a high prevalence of HF among acute ischemic stroke patients. Older patients with a history of hypertension and previous MI are at higher risk. Since patients with HF have a higher mortality and morbidity rate after experiencing an ischemic stroke, close cooperation between the neurology and cardiology specialists for providing advanced care for survivors is required.